Polarographic Studies on Mixed-Ligand Complexes of Lead(II) with DL-3-(3-,4-Dihydroxy Phenyl) Alanine and Some Dicarboxylic Acids - Kumar Singh, Sudesh; Chandel, C.P. (Asian Journal of Chemistry, 2010)
The polarographic reduction of lead(II) in the aqueous solution of DL-3-(3,4-dihydroxy phenyl) alanine (DL-DOPA) and some dicarboxylic acids (maleate and succinate) has been carried out. The stability constants have been determined for the simple Pb-DOPA system first, and then the mixed-ligand complexes of lead with DOPA and dicarboxylic acids (maleate and succinate) have been studied polarographically. The stability constant of mixed-ligand complexes have been determined by the method of Schaap and McMasters at 303 ± 3 K and ionic strength of 1.0 M. For the comparison of the stability of simple and mixed complexes, the mixing constant (Km) and stabilization constant (Ks) have been measured. The positive values of the mixing constants and stabilization constants show that the ternary complexes are more stable than the binary complexes.